2019
DOI: 10.1017/s0007114519000916
|View full text |Cite
|
Sign up to set email alerts
|

Oxylipin concentration, but not fatty acid composition, is altered in human donor milk pasteurised using both thermal and non-thermal techniques

Abstract: Human donor milk (DM) is Holder pasteurised (62·5°C, 30 min) to ensure its microbiological safety for infant consumption. In low-resource settings, flash heating is used to pasteurise milk. Although there is considerable interest in non-thermal alternatives (high hydrostatic pressure processing (HHP) and UVC irradiation) for pasteurisation, their effect on the fatty acid composition is not well understood. Of particular interest is the effect of pasteurisation on the generation of oxylipins. DM from eight moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 26 publications
3
29
1
Order By: Relevance
“…Our results are in general agreement with a study by Pitino et al, which reported significant reductions in human milk oxylipins following thermal (holder pasteurization, flash heating) and non-thermal treatments (High Hydrostatic Pressure and UVC) [33]. The authors reported minimal changes (not statistically significant) in the concentrations of LA and ALA metabolites following Holder (62.5°C for 30 min) and flash heating pasteurization compared with raw milk, consistent with our findings showing no significant changes in LA-and ALA-derived oxylipins as the result of BP (same processing conditions were used in both studies, 62.5°C for 30 min).…”
Section: Oxylipin Concentrationssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in general agreement with a study by Pitino et al, which reported significant reductions in human milk oxylipins following thermal (holder pasteurization, flash heating) and non-thermal treatments (High Hydrostatic Pressure and UVC) [33]. The authors reported minimal changes (not statistically significant) in the concentrations of LA and ALA metabolites following Holder (62.5°C for 30 min) and flash heating pasteurization compared with raw milk, consistent with our findings showing no significant changes in LA-and ALA-derived oxylipins as the result of BP (same processing conditions were used in both studies, 62.5°C for 30 min).…”
Section: Oxylipin Concentrationssupporting
confidence: 93%
“…The authors reported minimal changes (not statistically significant) in the concentrations of LA and ALA metabolites following Holder (62.5°C for 30 min) and flash heating pasteurization compared with raw milk, consistent with our findings showing no significant changes in LA-and ALA-derived oxylipins as the result of BP (same processing conditions were used in both studies, 62.5°C for 30 min). However, the significant reduction in LA and ALA metabolites observed in our study as a result of the HTST treatment was not observed by Pitino et al [33]. In addition to different starting materials used in both studies (human vs. bovine milk), different conditions were used for HTST treatment, which could explain the different outcomes.…”
Section: Oxylipin Concentrationscontrasting
confidence: 81%
“…An interest in human milk bioactive lipid Supporting information Additional supporting information may be found online in the Supporting Information section at the end of the article. mediators has emerged since oxidized metabolites of polyunsaturated fatty acids (PUFA), known as oxylipins, have been detected in human breast milk (Pitino et al, 2019;Robinson et al, 2017;Weiss et al, 2013;Wu et al, 2016). Oxylipins have been shown to regulate infant development and immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Human milk provides nutritional, immunological, and neurodevelopmental benefits for newborn infants (Harding et al, 2017). An interest in human milk bioactive lipid mediators has emerged since oxidized metabolites of polyunsaturated fatty acids (PUFA), known as oxylipins, have been detected in human breast milk (Pitino et al, 2019; Robinson et al, 2017; Weiss et al, 2013; Wu et al, 2016). Oxylipins have been shown to regulate infant development and immunity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation